2020
DOI: 10.1037/pne0000197
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Screening (TRIACOG) for adults with cerebrovascular diseases: Construction process and validity evidence.

Abstract: This study presents the construction process of the Cognitive Screening Instrument (TRIACOG) for evaluating poststroke adults. The TRIACOG has undergone a rigorous developmental process: (a) literature review; (b) analysis of the most sensitive items on a brief neuropsychological evaluation to differentiate between clinical and healthy cases; (c) addition of items; (d) content analysis by expert judges; (e) reformulation of the instrument; (f) pilot study; (g) reformulation of the instrument; (h) a second pilo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 42 publications
1
6
0
2
Order By: Relevance
“…Control participants were members of the general community and were recruited following the same steps as those employed by Rodrigues et al (2020) in the construction and investigation of validity evidence for the TRIACOG. Illiterate individuals, those with poor performance in the Mini Mental State Examination -MMSE (using a cut-off point adjusted for education: 22 points for individuals with up to 7 years of formal education and 23 points for those with 8 to 11 years of formal education; Kochhann et al, 2010), and those who scored above 9 points on the BDI-II screening test for depressive symptoms (Gorenstein et al, 2011) were excluded from the control group.…”
Section: Participantsmentioning
confidence: 99%
See 4 more Smart Citations
“…Control participants were members of the general community and were recruited following the same steps as those employed by Rodrigues et al (2020) in the construction and investigation of validity evidence for the TRIACOG. Illiterate individuals, those with poor performance in the Mini Mental State Examination -MMSE (using a cut-off point adjusted for education: 22 points for individuals with up to 7 years of formal education and 23 points for those with 8 to 11 years of formal education; Kochhann et al, 2010), and those who scored above 9 points on the BDI-II screening test for depressive symptoms (Gorenstein et al, 2011) were excluded from the control group.…”
Section: Participantsmentioning
confidence: 99%
“…In a previous study, interpretations of the TRI-ACOG showed validity evidence and significant performance differences in all tasks between post-stroke patients and healthy individuals. Patients' performance was worse compared to a group of healthy individuals, with effect sizes ranging from medium to large for most tasks (Rodrigues, Salles, & Bandeira, 2020). That study controlled for the effects of age and education on participants' performance in comparative analyses of performance differences between poststroke patients and the control group (Rodrigues, Salles, & Bandeira, 2020).…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations